World Food Security A History since 1945 - Shaw, D.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2007)
This book is the first comprehensive account of the numerous attempts made since the Second World War to provide food security for all. It provides a reference source for all those involved and interested in food security issues.
Keywords: Development economics; Urban economics; International economics; Macroeconomics; Development Economics; Urban Economics; International Economics; Macroeconomics/Monetary Economics//Financial Economics